Preoperative wound bed preparation with Ayurvedic management followed by split-thickness skin grafting in a post-debridement wound of the right lower leg: a case report - Pranav P. Naikwade; Rushikesh R. Solav; Pooja D. Moje; Vaishnavi B. Charhate; Rishabh S. Singh (International Journal of Basic & Clinical Pharmacology, 2026)
Large post-debridement wounds are often associated with infection, tissue loss, oedema, unhealthy granulation and delayed recovery, making their management challenging. Adequate preparation of the wound surface before grafting is important for successful healing. This case report describes the management of a post debridement wound of the right lower leg using Ayurvedic wound care measures followed by split-thickness skin grafting (STSG) with vacuum-assisted closure (VAC). A 62-year-old female presented with wounds over the posteromedial region of the right leg and ankle joint after trauma complicated by cellulitis and surgical debridement. Examination revealed slough, foul odour, irregular margins, exposed tendons and muscles, swelling and pain. Preoperative treatment included Panchavalkala Kashaya Dhavana and internal Ayurvedic medications aimed at wound cleansing and promotion of healthy granulation tissue. After improvement in the wound condition, STSG was performed and VAC therapy was applied with continuous negative pressure. Gradual reduction in pain, discharge, oedema, and unhealthy tissue was observed. Healthy granulation developed before grafting, and satisfactory graft uptake was noted during follow-up, with complete healing achieved subsequently. This case indicates that wound bed preparation with Ayurvedic management along with surgical intervention may contribute positively in healing.